ADOPTION OF DIGITAL MARKETING STRATEGIES BY STUDENT ENTREPRENEURS IN ENTREPRENEURIAL UNIVERSITY: DETERMINANTS AND CHALLENGES - Neihsial, H Lamminlun; Bhardwaj , Broto (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The purpose of the paper is to identify the various determinants and challenges in adoption of digital marketing strategies that can provide the platform for the student entrepreneurs to launch their products and services to digital customers in entrepreneurial university. The research mixed methodology includes the various case study mixed method that allows the researcher to examine the various mixed methodologies of creating the digital marketing platform for the student entrepreneurs for their products and services. The findings suggest that the student entrepreneurs can use the digital marketing platform including Faceresearch paper, Instagram and Google other platforms to launch their businesses online mostly free of cost till they can acquire their first customer. Then they can go ahead with expansion of their products and services to larger audience. The implications include the various tools of digital marketing and their applications for enhancing SMEs and small business during their launch. The student implications include the encouragement to the student entrepreneurs for enhancing their business and self-generating business.